The Relationship of Severity Level of Autism and Parent’s Unconditional Love on Children with Autism Moderated by Religiosity and Social Support - Neneng Tati Sumiati; Syanindia Annisa Dewi (Jurnal Psikologi, 2021)
Children with autism have difficulties in social interaction, lack of communication, and repetitive behavior. Thoseconditions make parents come to grips with several drawbacks in taking care of their autistic children. Thepurpose of this study was to determine the relationship between the severity level of autism and the unconditionallove of parents, moderated by religiosity and social support. This study was using a quantitative approach withstructural equation model (SEM) analysis. Participants in this study were 200 parents of children with AutismSpectrum Disorder (ASD) aged 2-17 years old and were selected by the non-probability sampling technique. Themeasurements applied in this study were unconditional love scale, taken from Porter Parent Acceptance scale,which consists of four items (α = .802; AVE = .628), social support scale, which consists of three items (α = .703;AVE= .628), Brief Multidimensional Measure of Religiousness/Spirituality, which consists of ten items (α =.952; AVE= .699), and Childhood Autism Rating Scale, which consists of four items (α = .756; AVE= .574). Theresult indicated that the unconditional love of parents was significantly affected by severity level of autism, b = -.162; t(196) = 2.849, p = .005; religiosity, b = .534; t(196) = 7.101, p = .000; and social support, b = .157; t(196)= 2.426, p = .016. Religiosity was proven to be essential in moderating the relationship of severity level of autismand unconditional love, b = .249; t(196) = 3.262, p = .001); while social support was not, b = -.020; t(196) = .293,p = .770. Religiosity could help maintain the unconditional love of parents for their autistic children, while socialsupport was not enough to buffer stress caused by them. Thus, parents of children with autism are urged toincrease their level of religiosity